An Analysis Of Word Formation By Using Apostrophes Found In Maroon 5 Album - Dewi Ratih, Khasviani, Drs. Sigit Haryanto,M.Hum, Siti Fatimah, S. Pd, M. Hum (2015)
This research is about word formation by using apostrophes analysis used in Maroon 5 album. The objectives are 1) to identify the formation by using apostrophes found in Maroon 5 album, and 2) to analyze the word formation with apostrophes in the English songs lyrics of Maroon 5 album. In this research, the writer uses a descriptive qualitative as the type of the research. Based on the result of research finding the researcher identifies and describes eight words that belong to apostrophes with nouns to show possessions. Those finding is tomorrow's. Then, the researcher identifies and describes thirty four words that belong to apostrophes to form constructions. Those findings are can't. I'm, I'll, I'd, I've, don't, it's, you're, wasn't, we'll, isn't, couldn't, won't, we're, she'll, doesn't, why'd, haven't, didn't, you'll, ain't, wouldn't, you've, what's, who's, girl's, she's, heart's, everybody's, candle's, nothing's, back's, that's and there's . After that, the researcher didn't find any data by using apostrophes in the song lyrics by Maroon 5 album. The data are lyrics including word formation by using apostrophes that can be found in Maroon 5 Album. She applies observation and documentation methods to collect the data. Based on the result of the analysis, 481 data of words containing apostrophes in the English song lyrics album by Maroon 5. It consists of 1 data apostrophes with nouns to show possession, 480 data of apostrophes to form construction, and no data containing of apostrophes to form plurals. The use of reference as the dominant type of using apostrophes because the data sources of research are the lyrics that basically bring the information to the reader.